An Electrochemical Study on the Cathode of the Intermediate Temperature Tubular Sodium-Sulfur (NaS) Battery. Issue 2 (12th January 2019) - Nikiforidis, G.; Jongerden, G. J.; Jongerden, E. F.; van de Sanden, M. C. M.; Tsampas, M. N.
Abstract : The development of low-cost energy storage schemes is imminent in light of the ever-growing demand of electricity. Sodium-sulfur (NaS) batteries offer low-cost technology for energy storage applications due to the intrinsically high capacities of elemental sodium and sulfur as well as their abundant resources. Operating this battery technology on the intermediate range (130–200°C) can lead to lower material costs, mitigate thermal management and safety issues and enhance cycle life. Herein, an electrochemical study on the cathode of the IT NaS cell is performed at 150°C and a concentration range of 1.5 to 3 M sodium pentasulfide dissolved in tetraglyme, showing a robust long term performance (42 days of continuous cycling) with a volumetric energy density of 83 Wh L −1 . Most importantly, the cell was eligible for a tenfold volume scale-up considerably enhancing its capacity (790 mAh) but in the same time somewhat hindered by mass transport, especially during the end of the discharge process as manifested by electrochemical impedance spectroscopy.